Tracking adipogenic differentiation of skeletal stem cells by label-free chemically selective imaging. Issue 12 (21st September 2015) - Smus, Justyna P.; Moura, Catarina Costa; McMorrow, Emma; Tare, Rahul S.; Oreffo, Richard O. C.; Mahajan, Sumeet
Abstract : CARS imaging proves to be a powerful, sensitive and label-free tool for studying adipogenesis in skeletal stem cells. Abstract : Coherent anti-Stokes Raman scattering (CARS) is a chemically selective label-free imaging technique which is rapidly emerging as a powerful alternative to conventional microscopy in biomedicine. The strength of this imaging approach is the provision of rapid insight into chemical distribution especially of small biomolecules such as lipids. The label-free, non-destructive and non-invasive nature of CARS lends itself for use with stem cells, as labelling or staining will render them otherwise unsuitable for therapy. Isolation, enrichment and characterisation of skeletal stem cells (SSCs) and their progeny is of tremendous significance in regenerative medicine. However, SSCs differentiation into bone, cartilage or fat cell types, is currently assessed using several invasive and, typically, destructive methodologies. Thus, CARS presents an exciting alternative to interrogate the differentiation of SSCs in their natural state. In the current study, we have examined the adipogenic differentiation of SSCs over time using CARS imaging and verified the observed differentiation using molecular analysis of gene expression as well as compared the results to conventional Oil Red O lipid staining. We find that the CARS analysis provides an enhanced resolution and definition of lipid droplets, detectable as early as 24 hours and 72 hours after adipogenic induction. Quantification of the CARS image data sets also showed a change in lipid droplet size distribution during the course of adipogenesis over 14 days. Furthermore, CARS provided a superior and facile approach to monitor changes in SSCs as a result of chemical modulation of adipogenic differentiation. The current studies pave the way for the use of CARS as a powerful chemical imaging tool in therapeutics, regenerative medicine and skeletal stem cell biology.